Guest editorial: Entrepreneurship and resource-based view: Emerging issues, new trends and innovative decision support tools - Carayannis, E. G.; Ferreira, F. A. F. (Management Decision, 2025)
Novel tools for facilitating entrepreneurial endeavors and aiding decision-making emerge on a daily basis, emphasizing the necessity for a fresh perspective on firm resources and capabilities. The resource-based view (RBV) (Barney, 1991) stands as a managerial framework employed to identify the strategic resources and capabilities firms can harness to attain sustainable competitive advantages, thereby bolstering both internal and external strategies. Within this context, problem structuring methods (PSM) and multiple criteria decision-making/analysis (MCDM/A) have garnered increasing attention over the last two decades and hold significant potential. This is evidenced by a marked growth in the number of published applications utilizing a formal approach to problem structuring in tandem with an analytic method for multi-criteria analysis (Marttunen et al., 2017).